2000
DOI: 10.1093/ps/79.10.1401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early age feed restriction on subsequent response to high environmental temperatures in female broiler chickens

Abstract: This study was conducted to determine whether early age feed restriction improves heat tolerance in female broiler chickens. Chicks were brooded for 3 wk and then maintained at 24+/-1 C. On Day 0, chicks were assigned to one of four feeding regimens; each regimen was applied to four cages of chicks. The feeding regimens were 1) ad libitum feeding (ALF); 2) 40% feed restriction at 4, 5, and 6 d of age (F40); 3) 60% feed restriction at 4, 5, and 6 d of age (F60); and (4) 80% feed restriction at 4, 5, and 6 d of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 23 publications
5
45
1
4
Order By: Relevance
“…Therefore, the content of HSP70 is often used as a specific indicator of stress. Zulkifli et al (2000) found that early age feeding restriction may improve heat tolerance in female broiler chickens from 35 to 41 days of age during which all birds were exposed to 38 • for 2 h day −1 . The results indicate that the 60 % feed restriction was beneficial for alleviating the detrimental effects of heat stress in female broiler chickens.…”
Section: Z Chen Et Al: Effects Of γ -Aminobutyric Acidmentioning
confidence: 97%
“…Therefore, the content of HSP70 is often used as a specific indicator of stress. Zulkifli et al (2000) found that early age feeding restriction may improve heat tolerance in female broiler chickens from 35 to 41 days of age during which all birds were exposed to 38 • for 2 h day −1 . The results indicate that the 60 % feed restriction was beneficial for alleviating the detrimental effects of heat stress in female broiler chickens.…”
Section: Z Chen Et Al: Effects Of γ -Aminobutyric Acidmentioning
confidence: 97%
“…Similarly, plasma total protein and albumin are significantly decreased in either quantitative (fed 85 and 70 % of feed intake by the control group) or qualitative FR (fed 85 and 70 % of the energy control diet). However, at 35 d of age these blood traits were higher in the qualitative FR groups (36) . FR regimen did not negatively affect liver leakage (AST and ALT enzymes), protein metabolism and renal function (creatinine) and welfare of chickens (cortisone) at 14 (end of restriction period) and 35 d of age (end of realimentation period) and markers of liver leakage (40) .…”
Section: Etabolic Profilesmentioning
confidence: 74%
“…However, the decrease of TAC with advanced age of chickens may indicate the use of antioxidants for antibody production during the transient period. Similarly, antibody to NDV of ad libitum fed chickens declined with duration of stress (36) . H-L ratio and tonic immobility duration were higher at 41 d of age in broilers fed ad libitum than those FR for 4 h per day from 7 to 21 d and fed ad libitum thereafter (23) , and FR induced stress on WBC during only the FR period (37,38) .…”
Section: Resultsmentioning
confidence: 93%
“…It is known that feed restriction increases the serum concentration of glucocorticoids (Zhan et al, 2007), which leads to the detachment of heterophils from the endothelium of the blood vessel and migration to the tissues (Gross & Siegel, 1988;Zulkifli et al, 1995). Moreover, the feed restriction in poultry increases the heterophil/lymphocyte ratio, so the number of migrant heterophils is even higher (Zulkifli et al, 2000;Jones et al, 2005). The lower growth rate, the reduction of haematocrit value and the beneficial effect of feed restriction on the cardiovascular system facilitate the migration of heterophils to the tissues, such as the gastrointestinal tract (Zubair & Leeson, 1994;Balog et al, 2000).…”
Section: Discussionmentioning
confidence: 99%